2018
DOI: 10.1002/hbm.24458
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal dynamics enable the functional differentiation of resting state networks in the human brain

Abstract: Intrinsic brain activity is organized in spatial-temporal patterns, called resting-state networks (RSNs), exhibiting specific structural-functional architecture. These networks presumably reflect complex neurophysiological processes and have a central role in distinct perceptual and cognitive functions. In this work, we propose an innovative approach for characterizing RSNs according to their underlying neural oscillations. We investigated specific electrophysiological properties, including spectral features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 98 publications
(123 reference statements)
5
48
3
Order By: Relevance
“…Moreover, it has been demonstrated that higher values of FD correspond to the presence of higher frequencies in the signal's Fourier spectrum and vice versa. [50][51][52] This relationship might not be linear: in our previous EEG study, 9 we showed that it was rather quadratic. There are many methods used to calculate FD, but the widely accepted ones are Katz's and Higuchi's methods, respectively, 24,53 with the latter considered the most accurate to estimate FD.…”
Section: -5mentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, it has been demonstrated that higher values of FD correspond to the presence of higher frequencies in the signal's Fourier spectrum and vice versa. [50][51][52] This relationship might not be linear: in our previous EEG study, 9 we showed that it was rather quadratic. There are many methods used to calculate FD, but the widely accepted ones are Katz's and Higuchi's methods, respectively, 24,53 with the latter considered the most accurate to estimate FD.…”
Section: -5mentioning
confidence: 79%
“…in the absence of external stimulation and response demands) have consistently been documented to be organized into large-scale networks, [1][2][3][4] each of them characterised by specific structural and functional architectures. [5][6][7][8] These are known as resting-state networks (RSNs), and have been widely reported in numerous neuroimaging 5,6 and electrophysiological [9][10][11][12] studies. The spatial pattern of RSNs is stable within individuals, consistent across healthy subjects and yet also contains considerable characteristic information about individuals' brain function [13][14][15] making them a powerful tool for neuroscientific enquiry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FD2, FD3, FD4, …., FD24). These three measures were averaged to give one mean value of FD for each k, for each subject [30][31][32]. The process was then repeated for every subject and every RSN.…”
Section: Characterization Of the Bold Rsns By Higuchi's Fractal Dimenmentioning
confidence: 99%
“…FD2, FD3, FD4, …., FD24). These three measures were averaged to give one mean value of FD for each k, for each subject [14,38,39]. The process was then repeated for every subject and every RSN (in Porcaro and colleagues [40] it is shown in detail the procedure and additional analyses demonstrating that the FD measurements were not dependent on the choice of window length or overlapping windows).…”
Section: Characterization Of the Bold Rsns By Higuchi's Fractal Dimenmentioning
confidence: 99%